Assessing the intelligence of a student through TIC-TAC-TOE game for career guidance - Sastry Kodanda Rama Jammalamadaka; Chandra Prakash Vudatha (Institute of Advanced Engineering and Science, 2019)
In order to provide Career Guidance by an expert system to a student, apart from his/her academic record, it is necessary to assess various psychological factors of the student like Intelligence, patience and perseverance, Learning ability and Speed of solving problem, etc. The outcome of this research work is an expert system called Tic-Tac-Toe Game Playing Career Guidance System (TTT-GP-CGS) that is useful to assess the psychological factors of the student through Tic-Tac-Toe Game Playing, build the cognitive model of the student and predict the appropriate career(s) for the student. The system plays Tic-Tac-Toe game with the student several times. The average score obtained by the student reflects his/her intelligence. The average time taken by the student for playing the game reflects student's speed of solving problem. The number of attempts the student makes reflects the students patience and perseverance. When the student plays the game with the spaystem every day, if the student's score increases day by day, it reflects that the student has good learning ability. In this way the system will assess the psychological factors of the student and builds the cognitive model of the student. Internally the system converts the quantitative scores into qualitative scores. The system maintains a table of careers and the expected levels of psychological factors that are required from student's side to carry out the career successfully. The system invokes a matching process by considering the cognitive model of the student and the table of careers, and predicts the career(s) suitable to the student.